2016
DOI: 10.3389/fpls.2016.01343
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide and Polyamines Act as Double Edged Swords in Plant Abiotic Stress Responses

Abstract: The specific genetic changes through which plants adapt to the multitude of environmental stresses are possible because of the molecular regulations in the system. These intricate regulatory mechanisms once unveiled will surely raise interesting questions. Polyamines and hydrogen peroxide have been suggested to be important signaling molecules during biotic and abiotic stresses. Hydrogen peroxide plays a versatile role from orchestrating physiological processes to stress response. It helps to achieve acclimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 149 publications
4
78
0
Order By: Relevance
“…Although the specific roles of polyamines in plant–microbe interactions are uncertain, there are hints. When polyamines contribute to plant defense, it is often because their catabolism releases the plant defense signal H 2 O 2 (Marina et al ., ; Jiménez‐Bremont et al ., ; Gupta et al ., ). Although R. solanacearum induces putrescine catabolism in a resistant host (Aribaud et al ., ), we found that the activity of the putrescine catabolism enzyme diamine oxidase was 2.3‐fold repressed in R. solanacearum ‐infected versus healthy tomato plants.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Although the specific roles of polyamines in plant–microbe interactions are uncertain, there are hints. When polyamines contribute to plant defense, it is often because their catabolism releases the plant defense signal H 2 O 2 (Marina et al ., ; Jiménez‐Bremont et al ., ; Gupta et al ., ). Although R. solanacearum induces putrescine catabolism in a resistant host (Aribaud et al ., ), we found that the activity of the putrescine catabolism enzyme diamine oxidase was 2.3‐fold repressed in R. solanacearum ‐infected versus healthy tomato plants.…”
Section: Discussionmentioning
confidence: 97%
“…Plants accumulate putrescine and other polyamines during drought (Gupta et al, 2016). Because drought stress and bacterial wilt disease both cause wilting, we investigated whether other wilt pathogens also triggered putrescine accumulation.…”
Section: R Solanacearum Produces Putrescine In Tomato Xylem Sap and mentioning
confidence: 99%
See 3 more Smart Citations